GAMBARAN TINGKAT PENGETAHUAN SISWA/SISWI SMA MUHAMMADIYAH 01 MEDAN TERHADAP PENGGUNAAN LENSA KONTAK KOSMETIK - DIMAS ANGGA PRATAMA; ZALDI Z (JURNAL ILMIAH SIMANTEK, 2021)
Contact lenses are visual aids other than glasses. Cosmetic use as a beauty tool and is made to support the appearance ofthe eye. Problems caused by contact lens wear depend on factors such as lens material, lens cleanliness, type of lenswashing fluid, level of lens user knowledge in lens usage. To determine the level of knowledge of the students of SMAMuhammadiyah 01 Medan on the use of cosmetic lens contacts. The type of research used is observational descriptiveresearch with a cross-sectional design. From 86 respondents obtained an overview of the level of knowledge of students ofMuhammadiyah 01 Medan High School on the use of cosmetic contact lenses with good knowledge there were 34respondents (39.5%), sufficient knowledge of 45 respondents (52.3%) and less knowledge there were 7 respondents (8.1%).Based on gender who are well knowledgeed are women with 21 respondents (48.8%). The results of this study show anoverview of the level of knowledge of students of Muhammadiyah 01 Medan High School regarding the use of cosmeticcontact lenses with the most knowledgeable.